COMPARISON OF OUTCOMES ON LIKE EXAMS ADMINISTERED TO IN-RESIDENCE AND ASYNCHRONOUS DISTANCE-BASED PHARM.D. STUDENTS - Ragan, Ronald E.; Kleoppel, James W. (Online Learning, 2004)
The purpose of this retrospective study was to compare the academic outcomes of distance-based students in the asynchronous non-traditional pathway with in-residence students in the traditional pathway on examples of like examinations in the Pharm.D. curriculum at the Kansas University School of Pharmacy. This study evaluated the commitment of assuring equivalent outcomes for students in non-traditional and traditional Pharm.D. pathways, as stipulated by the School of Pharmacy accrediting body, the American Council on Pharmaceutical Education (ACPE). Similar examinations were administered to both groups of students. Scores were evaluated using the Student t-Test and ANOVA. This study demonstrates that average test scores of distance-based students were equal to or higher than their counterpart in-residence students when tested on physical assessment content.